1977
DOI: 10.1002/ajpa.1330470107
|View full text |Cite
|
Sign up to set email alerts
|

Gm and Inv studies on baboons,Papio cynocephalus: Analysis of serum samples from Kenya, Ethiopia and South Africa

Abstract: Serum samples from 526 baboons (Papio cynocephalus) from 10 troops from the Laikipia district of northern Kenya, from 60 baboons from two troops from the Awash National Park, central Ethiopia, and from 127 baboons from South Africa were tested for Gm and Inv allotypes. Four of the 10 troops from Kenya formed a western cluster and six formed an eastern cluster. The clusters were separated by approximately 10 miles.The samples were tested for Gm (1,2,3,5,6,11, 13,14,15, 16,17,21,24) and for Inv (1, 2, 3). All sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1978
1978
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…Km(3) however is more ancient, being isotypic in all apes analyzed by VAN LOGHEM and DE LANGE (1979) and also in P. cynocephalus in Kenya (STEINBERG et al, 1977). Using Gm and Km allotype polymorphisms, proposals have been made as to the evolution of the IgG system (RtVAT et al, 1974;VAN LOGHEM, 1984).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Km(3) however is more ancient, being isotypic in all apes analyzed by VAN LOGHEM and DE LANGE (1979) and also in P. cynocephalus in Kenya (STEINBERG et al, 1977). Using Gm and Km allotype polymorphisms, proposals have been made as to the evolution of the IgG system (RtVAT et al, 1974;VAN LOGHEM, 1984).…”
Section: Discussionmentioning
confidence: 96%
“…The allotypes G3m(t), (u), A2m(1), and (2) are absent in all species, as are Glm(f), G2m(n), G3m(g), and Km(2), except for rare exceptions. Glm(f) has only been described in baboons and macaques by LITWlN (1969), RIVAT et al (1968RIVAT et al ( , 1969, STEINBERG et al (1977), and GAARDER and NATV~G (1974) have found it in the Hominoidea, but not in gibbons. G3m(bl) and Km(3) are also infrequent.…”
Section: Gm Km and Am Polymorphismsmentioning
confidence: 92%
“…One can determine paternity exclusions among monkeys, although I have not yet heard of any resulting lawsuits from nonpaternity. Steinberg et al (1977) reviewed Gm samples from ten troops of baboons in Northern Kenya and suggested that variation in haplotype frequencies is the result of founder effect largely due to fission of a large troop into two smaller ones. Duggleby (1978) reported genetic differentiation of social groups among the macaques on Cay0 Santiago.…”
mentioning
confidence: 99%
“…Many authors have also tested the pres ence of antigenic determinants of Ig (epi topes) in sera of various nonhuman primates [Alepa and Terry, 1965;Alepa, 1969;Litwin, 1969;Rivât et al, 1968Rivât et al, , 1969RufTié and Blanc, 1972;Gaarder and Natvig, 1974;Van Loghem et al, 1968Van Loghem and Litwin, 1972;Van Loghem and de Lange, 1979;Shuster et al, 1970;Steinberg et al, 1977;Olivier et al, 1986]. All studies report the distributions of Ig allotypes for samples of various origins, including populations lo calized in small geographic areas.…”
Section: Introductionmentioning
confidence: 99%